2004
DOI: 10.1038/sj.leu.2403597
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of acute promyelocytic leukemia treated with all trans retinoic acid and chemotherapy in elderly patients: the European group experience

Abstract: We analyzed the outcome of patients aged more than 60 included in a multicenter trial in newly diagnosed acute promyelocytic leukemia (APL93 trial), which tested the role of early addition of chemotherapy to all trans retinoic acid (ATRA) and of maintenance with ATRA and/or low-dose chemotherapy. In total, 129/533 (24.2%) patients included in this trial were older than 60. The CR rate was 86% in patients older than 60 as compared to 94.5% in younger patients (P ¼ 0.0014), due to a higher incidence of early dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 15 publications
(18 reference statements)
4
41
2
Order By: Relevance
“…Using idarubicin, mitoxantrone, and ATRA, Sanz et al noted that 6 of 25 patients aged 70 years and older died in remission, 14 while Ades et al reported that 19% of patients aged 60 years and older died due to complications of myelosuppression during consolidation with daunorubicin plus cytarabine. 15 These observations have led Fenaux et al 16 and LoCoco et al 17 to propose attempts to reduce the intensity of chemotherapy, at least in older patients with low-risk untreated APL. The data in Table 4 suggest that use of ATO plus ATRA may be an alternative to typical consolidation chemotherapy in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Using idarubicin, mitoxantrone, and ATRA, Sanz et al noted that 6 of 25 patients aged 70 years and older died in remission, 14 while Ades et al reported that 19% of patients aged 60 years and older died due to complications of myelosuppression during consolidation with daunorubicin plus cytarabine. 15 These observations have led Fenaux et al 16 and LoCoco et al 17 to propose attempts to reduce the intensity of chemotherapy, at least in older patients with low-risk untreated APL. The data in Table 4 suggest that use of ATO plus ATRA may be an alternative to typical consolidation chemotherapy in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] We and others have shown that ATRA induces maturation followed by apoptosis in a variety of different cell lines. [5][6][7][8] Differentiation induced by binding of ATRA to its nuclear retinoid receptors is detectable within 24-48 h 9 followed by apoptosis at 72-96 h. 5 It has been shown that mitochondria play an important regulatory role in ATRA-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…10 Another sizable subset of patients die in CR from complications of consolidation treatment, mainly from infection due to chemotherapy-induced myelosuppression. 7,[11][12][13] To decrease mortality in CR, the Programa para el Estudio de la Terapéutica en Hemopatía Maligna (PETHEMA) group reduced the intensity of consolidation chemotherapy by avoiding cytosine arabinoside (AraC) in the chemotherapy regimen. 8,9 They observed CR rates comparable with regimens using a combination of AraC with anthracycline, a lower rate of death in CR (2%) and a low cumulative incidence of relapse (10%).…”
mentioning
confidence: 99%